2014
DOI: 10.1155/2014/461956
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Relative Waist Circumference between Asian Indian and US Adults

Abstract: Background. Relative to Europeans, Asian Indians have higher rates of type 2 diabetes and cardiovascular disease. Whether differences in body composition may underlie these population differences remains unclear. Methods. We compared directly measured anthropometric data from the Chennai Urban Rural Epidemiology Study (CURES) survey of southern Indians (I) with those from three US ethnic groups (C: Caucasians, A: African Americans, and M: Mexican Americans) from NHANES III (Third National Health and Nutrition… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

8
24
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 32 publications
(35 citation statements)
references
References 29 publications
(19 reference statements)
8
24
0
Order By: Relevance
“…We have demonstrated that South Asians have significantly reduced minimum and maximum LA volumes compared with Caucasians, even after correction for BSA. This is despite the fact that South Asians have a higher prevalence of risk factors for LA enlargement such as hypertension, diabetes mellitus, and obesity . Our study also shows that South Asians have lower LV mass, smaller LV EDV, and lower LV stroke volume compared with Caucasians.…”
Section: Discussionmentioning
confidence: 45%
“…We have demonstrated that South Asians have significantly reduced minimum and maximum LA volumes compared with Caucasians, even after correction for BSA. This is despite the fact that South Asians have a higher prevalence of risk factors for LA enlargement such as hypertension, diabetes mellitus, and obesity . Our study also shows that South Asians have lower LV mass, smaller LV EDV, and lower LV stroke volume compared with Caucasians.…”
Section: Discussionmentioning
confidence: 45%
“…Among the various anthropometric variables, the measurements of skinfold thicknesses (Freedman et al , Freedman, Ogden, Goodman, & Blanck, ), waist circumference (Bajaj et al, ), the conicity index (Shidfar, Alborzi, Salehi, & Nojomi, ) and body mass index (BMI) (Ranasinghe et al, ) are frequently used to determine body fat in epidemiological studies. Despite their logistic advantages, these techniques also have limitations, such as the inability to differentiate fat from fat‐free mass, a well‐known limitation of BMI (Clarys, Provyn, & Marfell‐Jones, ; Rahman & Berenson, ).…”
Section: Introductionmentioning
confidence: 99%
“…This "metabolically obese (visceral obesity)" phenotype among normalweight individuals in Asia, may explain the increased predisposition for diabetes, despite low prevalence of "obesity" in Asia. A collaborative study between researchers at the University of Minnesota and the staff of Madras Diabetes Research Foundation, Chennai, India, demonstrated this differential distribution of fat in Asian subjects compared to Caucasians, Afro-Americans and Hispanic populations [6]. Major metabolic contributors for the development of this chronic disorder are hyperglycemia, insulin resistance, dyslipidemia, hypertension, endothelial dysfunction, obesity, oxidative stress, and metabolic syndrome.…”
mentioning
confidence: 99%
“…Major metabolic contributors for the development of this chronic disorder are hyperglycemia, insulin resistance, dyslipidemia, hypertension, endothelial dysfunction, obesity, oxidative stress, and metabolic syndrome. Studies done at several research centers indicates, that this chronic disease by and large is preventable by diet, exercise and life style modification [6][7][8]. Professor Roy Taylor of Newcastle University has demonstrated that even well characterized cases of type-2 diabetes can be reversed by very low calorie diets [9].…”
mentioning
confidence: 99%
See 1 more Smart Citation